The truth about parrots - Eaton, Maxwell, III (Roaring Brook Press, 2021)
Featuring colorful, comic-style artwork, an introduction to parrots is presented through humorous text complemented by engaging facts, from how parrots see ultraviolet light to how they can identify colors in human language.